Assessment of urinary pharmacokinetics and pharmacodynamics of orbifloxacin in healthy dogs withex vivomodelling. Issue 5 (May 2017) - Shimizu, Takae; Harada, Kazuki; Manabe, Saki; Tsukamoto, Taku; Ito, Norihiko; Hikasa, Yoshiaki
Abstract : Purpose. : The aim of this study was to investigate the urinary pharmacokinetics (PK) of orbifloxacin (OBFX) administered at 5 mg kg −1 in six healthy dogs. A further aim was to use an ex vivo model to evaluate the urinary PK and pharmacodynamics (PD) of OBFX to determine its urinary bactericidal titre (UBT), which represents the maximal dilution of urine allowing bactericidal activity. Methodology. : Fourteen urinary tract infection (UTI) pathogenic strains of five bacterial species ( Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus mirabilis and Staphylococcus pseudintermedius ) were used. Urine samples were obtained every 4 h for the first 24 h after OBFX administration, for measurement of urine drug concentration and UBT. Results/Key findings. : The urine OBFX concentration peaked at 0‐4, 4‐8 or 4‐8 h after administration, with a maximum concentration of 383±171 μg ml −1 . Overall, the fluctuation in median UBT closely correlated with that of the mean urine OBFX concentration. In addition, the median areas under the UBT‐time curves (AUBTs) were significantly inversely correlated with the MICs for OBFX in the tested strains ( P <0.01). Notably, median UBTs and AUBTs were extremely low (0‐0.5 and 2‐5, respectively) in OBFX‐resistant E. coli strains with MIC ≥8 μg ml −1 . Conclusion. : The fluctuation of UBTs closely correlated with that of urine concentration, and UBT values depended on the susceptibility of the bacterial strains to OBFX. We believe that ex vivo modelling to determine UBTs is useful to evaluate the urinary PK/PD of antimicrobials indicated for UTIs in dogs.